Analisis Perbandingan Kinerja Metode Load Balancing Berbasis CPU Dengan Berbasis Response Time Pada Software Defined Network - Muharrom Abdillah; Widhi Yahya; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Server is part of important thing in a service inside computer network. the purpose of server can determine how fine the quality of the services. More request will make the server have more loads and decreasing performance of server. The solution is to use multiple servers that implement load balancing method, so that servers performance becomes more stable. Load balancing method implemented in software defined network. This architecture offers scalability and programmability for more complex network like load balancing for web server. There are any research about load balancing in SDN with several method implemented, they are round robin method, CPU usage based method and response time based method. This research give analysis to performance of round robin method, CPU usage based method and response time based method. The trial are doing to three categories of rates, they are low for rate 40, medium for rate 80 and high for rate 160. The trial are doing in 10 seconds for each rate. The parameters used in this trial are throughput and CPU usage. The throughput test resulting that round robin is excellent in low category with average value 32,64 KB/s, meanwhile in medium and high category response time method is more excellent with average values 65,02 KB/s and 115,50 KB/s. Whereas, in CPU usage test, CPU usage method have the lowest standart deviation with average values 3,95%, 4,69%, and 5,90%.